2020
DOI: 10.2147/ijn.s246724
|View full text |Cite
|
Sign up to set email alerts
|

<p>Anti-Metastatic Effect of Gold Nanoparticle-Conjugated <em>Maclura tricuspidata</em> Extract on Human Hepatocellular Carcinoma Cells</p>

Abstract: Purpose We aimed to study green-synthesized gold nanoparticles (GNPs) from Maclura tricuspidata (MT) root (MTR), stem (MTS), leaf (MTL), and fruit (MTF) extracts and evaluate their anti-metastatic properties in hepatocellular carcinoma cells. Maclura tricuspidata belongs to the Moraceae family and is widely used as a traditional medicinal plant given its biological activities. Methods We quantified the phenolic and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Park et al [82], determined the antimetastatic properties of M. tricuspidata root, stem, leaf, and fruit extracts with high phenol and flavonoid content and antioxidant capacity in hepatocellular carcinoma cells, showing that these extracts can be used in potential treatment for hepatocellular carcinoma with the possibility of improving therapeutic efficiency. Regarding the antimicrobial activity of M. tricuspidata, its effect on Streptococcus iniae has been studied [83], showing high inhibition and evidencing the role of prenylation of isoflavones from fruit and leaf extracts on its antibacterial activity.…”
Section: Maclura Tricuspidatamentioning
confidence: 99%
“…Park et al [82], determined the antimetastatic properties of M. tricuspidata root, stem, leaf, and fruit extracts with high phenol and flavonoid content and antioxidant capacity in hepatocellular carcinoma cells, showing that these extracts can be used in potential treatment for hepatocellular carcinoma with the possibility of improving therapeutic efficiency. Regarding the antimicrobial activity of M. tricuspidata, its effect on Streptococcus iniae has been studied [83], showing high inhibition and evidencing the role of prenylation of isoflavones from fruit and leaf extracts on its antibacterial activity.…”
Section: Maclura Tricuspidatamentioning
confidence: 99%
“… 2020 ; Lee and Choi 2020 ; Park et al. 2020 ). It is a traditional medicinal plant given its biological activities (Park et al.…”
mentioning
confidence: 99%
“…Maclura tricuspidate Carriere is a member of the Moraceae family, mainly distributed in Korea and East Asia (Choi et al 2020; Lee and Choi 2020;Park et al 2020). It is a traditional medicinal plant given its biological activities (Park et al 2020). It was found that M. tricuspidata fruit vinegar had antiinflammatory effect in vitro (Choi et al 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation